Financial Performance Analysis Using Economic Value Added (EVA), Financial Value Added (FVA), and Market Value Added (MVA): (A Study on Technology Sector Companies Listed on the Indonesia Stock Exchange from 2019-2023) - Hafilah Nurajrina; Rahmat Mulyana; Desmy Riani (Jurnal Mahasiswa Akuntansi dan Bisnis (JMAB), 2025)
Financial performance assessment is a process required by companies, especially investors, as a consideration in making investment decisions. This study aims to determine and analyze financial performance using the Economic Value Added (EVA), Financial Value Added (FVA), and Market Value Added (MVA) methods in technology sector companies listed on the IDX for the 2019-2023 period. This type of research is descriptive quantitative, with a purposive sampling technique from 44 technology sector companies, of which 4 companies were used as samples. The EVA results show that 4 companies, namely MCAS, MLPT, WIFI, and MTDL, obtained an average positive value (EVA>0) within 5 years. This indicated the company can generate economic value while avoiding long-term debt dependence. The FVA results for companies coded MCAS, MLPT, WIFI, MTDL obtained an average positive result in the 2019-2023 period, indicating that the company has succeeded in adding financial value and has been able to cover the company's equivalent depreciation value. and the MVA results for 4 technology sector companies that meet the research criteria, namely MCAS, MLPT, WIFI, MTDL, obtained positive results (MVA>0) in the 2019-2023 company. This indicates that the company has been able to create market added value for the company and investors. Keywords: Financial performance, EVA, FVA, MVA.